The Impact of AI-Driven Personalization on Learners` Performance - Das, Amit; Malaviya, Sanjeev; Singh, Manpreet (International Journal of Computer Sciences and Engineering, 2023)
This study explores the impact of AI-driven personalization on learners` performance. Through quantitative and qualitative analysis, the research demonstrates a positive correlation between personalized AI-based adaptive learning and improved academic achievement, engagement, and satisfaction. The findings highlight the potential of AI-driven personalization to enhance learners` performance and transform education practices.